The place of South Asia in the world economy: human-geographical, geo-economic and geopolitical aspects - Mamchur, Olha; Vanda, Iryna (Human Geography Journal, 2022)
The article deals with the positioning of South Asia in the world economy in the XXI century as its place in the flows of goods and services, finances, humans and technologies. The information base of the research is newest available statistical data of the UN institutions and the World Bank. Intraregional diversity as disparities between countries is shown. The entrenchment in the world economy is proved by GDP growth, dynamics of foreign trade and foreign direct investments. The main human-geographical features of the region are substantiated: asymmetricity with India as extremum, contrasts, and rather low transnationalization. Demographical and social, economic contrasts and geopolitical tensions of South Asia, that has deep historical and cultural roots, are distinguished. The structure of South Asia’s foreign trade is characterized by groups of goods and technological classification. The typical feature for the developing countries regions is the predominance in exports of low technologies and resources-based manufactures. The unique for South Asia is the high share of primary products in imports, that reflects food and raw material dependence. Based on the technological classification The last one applied for regarding the differentiation by countries in its ties with geographical factors. Geo-economic aspects are determined by the position among other macro-regions of the world, the degree of ties with geo-economic leaders, geographical features of international trade and investment flows. Economic integration is considered in the context of the functioning of the South Asian Association for Regional Cooperation, which includes all countries of the region. The potential growth of the role of interstate economic association for intensification of intra-regional ties is noted, which will also strengthen the position of South Asia in the world economy as a consequence. Conflicts between countries, political and ideological differences often do not contribute to the consolidation of efforts of the countries in the region. Staying in the sphere of influence of different global geopolitical players, as well as the interpretation of India as one of such actors, in particular its opposition to China, bring difficulties in strengthening the place of the region and, in particular, India, in the world economy.